Citizenship Education in the K to 12 Junior High School Economics Curriculum in the Philippines: A Content Analysis. (August 2022) - Dizon, Arnie G.
This study describes the integration of citizenship education into the K to 12 Junior High School Economics curriculum in the Philippines. Content analysis of the 2016 Curriculum Guide Learning Competencies (CGLCs) and 2020 Most Essential Learning Competencies (MELCs) for Social Studies was conducted to determine the alignment of the Economics curriculum with liberal individualist and civic republican conceptions of citizenship. Gaps that need to be addressed in the alignment of Economics learning competencies with citizenship education were explicated. Results of the study show that the Junior High School Economics curriculum integrates liberal individualist and civic republican conceptions of citizenship. However, civic-oriented outcomes like wastong pagbabayad ng buwis (correct payment of taxes) and bayanihan spirit (communal unity) need to be explicitly stated to ensure that these essential outcomes will not be missed out in the unpacking of the learning competencies.